PENGARUH PENDAPATAN ASLI DAERAH,INVESTASI SWASTA, DAN DANA PERIMBAGAN TERHADAP PERTUMBUHAN EKONOMI DI KOTA MAKASSAR PADA TAHUN 2003-2016 - Jumasrah Jumasrah (Jurnal Ekonomi Bisnis Syariah, 2018)
This study aims to determine the effect of local revenue, private investment and balance funds on economic growth in the city of Makassar in the year 2003-2016. Research location in makassar city and data collection center at BPS office (Central Bureau of Statistics) South Sulawesi. The data used is secondary data (Time Series) during the time period of 14 years (2003-2016). The result of research indicates that local revenue (PAD) has a positive and significant effect on economic growth, private investment has positive and significant impact on economic growth, and balance fund (DP) has negative and significant influence on economic growth in Makassar city.